Effect of Effectiveness of Operational Audit, Internal Control and Professionalism of Financial Management Apparatus on the Quality of Financial Statements at the BLUD RSUD dr. M. Yunus Bengkulu - Fachruzzaman Fachruzzaman; Aulia Permatasari; Abdullah Abdullah (Journal of Indonesian Management, 2021)
The purpose of this study was to determine whether the effectiveness of operational audits, internal controls and the professionalism of financial management officials had an effect on the Quality of Financial Statements in the BLUD of the RSUD dr. M. Yunus Bengkulu.This research is a comparative causal study with a quantitative approach. The data used in this study are primary data through answers to questionnaires from research respondents. Respondents of this study were financial management apparatus at the BLUD RSUD dr. M. Yunus Bengkulu. To obtain data, field research techniques are used with Documentation, namely collecting secondary data such as books, literature, leaflets and archives relating to the object of research, interviews to strengthen the author's arguments and distributing questionnaires. All data presentation and analysis used in this study used the SPSS program (Statistical Product and Service Solution). To test the questionnaire analyzes used validity test, reliability test, classic assumption test consisting of normality test, multicollinearity test and heterocedasticity test. The results of this study indicate that the effectiveness of operational audits, internal control and professionalism have a significant effect on the quality of financial reports in the BLUD of the RSUD dr. M. Yunus Bengkulu.